1994
DOI: 10.1007/bf02999857
|View full text |Cite
|
Sign up to set email alerts
|

Lipoproteins in hypoxic tumor cells as traps of free radicals

Abstract: We examined the role of main cell protective mechanisms in retaining the high resistance of ascitic cells (EAC, ZAH) to lipid peroxidation with respect to different stages of tumor-organism metabolic interactions. The following mechanisms were studied: (1) the activity of main EAC enzymatic antioxidants (GSH-Px, SOD); (2) changes in lipid metabolism, especially the content of the main PUFA (linoleic and arachidonic fatty acids) in EAC cells; (3) comparison of intracellular resistance between EAC/ZAH cytoplasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…(Fig.l). Earlier we have shown that these granules can act as traps for free radicals (19) and can protect whole stationary EAC cells against lethal oxidative injury by this pathway. These distinctions between normal and tumor cell resistance to oxidative stress Under conditions in which free radical actions in low energy cells are being continued, some cell proteins become modified by cross-linking.…”
Section: Resluts and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Fig.l). Earlier we have shown that these granules can act as traps for free radicals (19) and can protect whole stationary EAC cells against lethal oxidative injury by this pathway. These distinctions between normal and tumor cell resistance to oxidative stress Under conditions in which free radical actions in low energy cells are being continued, some cell proteins become modified by cross-linking.…”
Section: Resluts and Discussionmentioning
confidence: 99%
“…We have previously developed a method (7) for determination of the resistance of living cells and their intracellular compartments to oxidative stress that was induced through the action of UV-light (=365nm). All details of this method were presented in a series of our previous articles (7,8,13,19,20), together with a description of the measurement of spectrokinetic parameters in corresponding fluorescence spectra from single cells.…”
Section: Introductionmentioning
confidence: 99%
“…When UV is irradiated to lipid molecules, hydrogen molecule in double bond in LH (unsaturated fatty acids) is cut off and L• (lipid radical) is formed. When O 2 molecules are exist nearby, L• will be LOO•, which will make peroxide radicals (LOOH), activating membrane enzymes such as PLC and PLA2 [45][46][47][48].…”
Section: I-2 Effect Of Uv Light For Redox Signalingmentioning
confidence: 99%